Salivary Del‐1, IL‐17, and LFA‐1 levels in periodontal health and disease. (10th March 2020) - Inönü, Elif; Kayis, Seyit Ali; Eskan, Mehmet Akif; Hakki, Sema S.
Abstract: Objective and Background: Developmental endothelial locus‐1 (Del‐1), lymphocyte function‐associated antigen‐1 (LFA‐1), and interleukin 17 (IL‐17) play critical roles in transendothelial migration of neutrophils in periodontal diseases. The aim of this study was to evaluate salivary Del‐1, IL‐17, and LFA‐1 protein levels in patients with gingivitis (G), chronic periodontitis (CP), and generalized aggressive periodontitis (GAP). Methods: A total of 180 systemically healthy, non‐smoking patients (45 periodontally healthy (H) and 45 G, 50 CP, and 40 GAP) individuals (between March 2014 and February 2016) were included in this study according to Armitage's (1999) classification. Clinical periodontal parameters, including clinical attachment level, probing depth, plaque index, and gingival index, were recorded. Del‐1, IL‐17, and LFA‐1 protein expression levels were measured in unstimulated saliva samples collected from patients by using enzyme‐linked immunosorbent assays. Kruskal‐Wallis and Mann‐Whitney U tests were used for multiple comparisons and post hoc statistical analyses, respectively. ROC curve analysis was used to evaluate the sensitivity and specificity of Del‐1, IL‐17, and LFA‐1 in distinguishing periodontal disease from health and gingivitis. Results: It was found a high level of IL‐17 and a low level of Del‐1 in the CP and GAP, as compared to the G and H groups ( P  < .001). Nevertheless, we found LFA‐1 levels were higher in the GAP than in the CP or G groups ( P  = .00). Consistently, LFA‐1 levels were lower in the H and G groups than in the CP and GAP groups ( P  = .00). The combination of three biomarkers was found as the best predictor yielded exhibited the highest AUC [0.893, 0.845‐0.94 (%95 CI) P  < .001] in discriminating periodontal disease from health and gingivitis. Conclusion: Salivary Del‐1, LFA‐1, and IL‐17 levels might be useful markers for determining the clinical health and disease status of patients with periodontitis. However, further studies that evaluate the level of salivary Del‐1, LFA‐1, and IL‐17 before and after periodontal therapy are required to understand the exact roles of these cytokines during the periodontal healing period.